The mediating role of coping style in the relationship between fear of childbirth and psychological birth trauma among natural childbirth women in China: a structural equation model analysis - Ying Wang; Cuiping Liu; Yujie Sun; Yaqing Yuan; Liping Chen (BMC Pregnancy and Childbirth)
Abstract Background Psychological birth trauma represents a significant global public health concern, with an estimated 45% of new mothers reporting such an experience. Researchers mostly focus on the impacts of postpartum mental health issues, such as postpartum post-traumatic stress disorder, minimal attention has been given to the antecedents of psychological birth trauma. This study seeks to investigate the correlation between fear of childbirth and psychological birth trauma among Chinese women who have undergone natural childbirth, as well as the mediating role of coping styles in the association between fear of childbirth and psychological birth trauma. Methods This cross-sectional study was conducted among 420 women who underwent natural childbirth between June and December 2021 in Shandong Province, China. Data were gathered using the Wijma Delivery Experience Questionnaire, Trait Coping Style Questionnaire, and Impact of Event Scale-Revised. The structural equation model (SEM) was employed to examine the relationships between variables and to develop the final model. Results The prevalence of psychological birth trauma among women who had experienced natural childbirth was recorded at 10.27%. The mean score and standard deviation of psychological birth trauma, fear of birth, positive coping (PC), and negative coping (NC) among these women were 19.7 ± 12.5, 76.9 ± 21.3, 35.66 ± 7.05, and 28.20 ± 7.99, respectively. Findings indicated that women’s fear of childbirth was directly (B = 0.340, p = 0.001) and indirectly (B = 0.124, p = 0.001) linked to women’s psychological birth trauma. Additionally, women’s PC was negatively associated with psychological birth trauma (B= -0.352, p = 0.001), while NC was positively associated with psychological birth trauma (B = 0.199, p = 0.001). Conclusions Chinese women who experienced natural childbirth encountered a moderate level of psychological birth trauma. Women’s coping style plays a pivotal mediating role in the connection between fear of childbirth and psychological birth trauma. Consequently, interventions aimed at diminishing women’s fear of childbirth and enhancing PC skills should be devised and implemented to alleviate women’s psychological birth trauma.